Pemanfaatan Game Edukatif dalam Meningkatkan Minat Belajar Ekonomi di Kalangan Siswa Sekolah Dasar - Idris, M (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research examines the use of educational games as a strategy to increase interest in learning economics among primary school students. Through a comprehensive literature study, this research analyzes various data sources including relevant journals, articles and theoretical studies to evaluate the effectiveness of educational games in the context of economic education. The study results show that educational games can be an invaluable tool in educating students about basic economic concepts such as the value of money, exchange and efficient use of resources. The games not only add excitement to the learning process but also help students develop critical thinking and problem-solving skills. The study emphasizes the importance of good game design, which should match the learning objectives and be able to provide adequate feedback to students. In addition, this study suggests that teachers need to be trained to integrate the use of educational games with the existing curriculum to optimize economic learning outcomes. With the right approach, educational games have the potential to enrich the learning experience and support students in building a strong foundation in economics from an early age